Optimizing Employee Performance through Physical Work Environment Governance: A Study at the Probolinggo Social Service - Marwiyah, Siti; Maksin, Mastina; Queennensa, Mareta Syamsya (Master Program of Sociology, Universitas Malikussaleh,, 2025)
This study aims to analyze the influence of the physical work environment on improving employee performance in the delivery of public services at the Social Affairs Office of Probolinggo City. The physical work environment is a crucial factor that affects employee comfort, efficiency, and productivity. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis refers to the performance factor theory of Robert L. Mathis and John H. Jackson, as well as the Regulation of the Minister of Administrative and Bureaucratic Reform (Permenpan RB) No. 17 of 2017 concerning the Guidelines for Preparing the Professionalism Index of Civil Servants. The results indicate that aspects of the physical work environment—such as lighting, room temperature, cleanliness, spatial arrangement, and the availability of facilities and infrastructure—positively contribute to improving employee performance. A supportive work environment fosters a conducive atmosphere, enhances motivation, and accelerates public service delivery. Therefore, improving and maintaining the physical work environment is a strategic factor in efforts to enhance public service quality.